Managing Beliefs about Monetary Policy under Discretion - Elmar Mertens (Swiss National Bank, Study Center Gerzensee, 2008)
Monetary policy is most effective when public beliefs about future policies are actively managed. This is the appeal of policy rules and commitment strategies, typically absent under discretion. But when a policymaker has some private information - as is the case in reality - belief management becomes an integral part of optimal discretion policies, too. Solving for optimal policy in a simple New Keynesian model, this paper shows how discretionary losses are reduced when the policymaker has private information. Furthermore, disinflations are pursued more vigorously, when the hidden information problem is larger, even when inflation is partly backward-looking.
Keywords: E31; E37; E47; E52; E58; 330; Optimal Monetary Policy; Discretion; Time-Consistent Policy; Markov-Perfect Equilibrium; Incomplete Information; Kalman Filter; Geldpolitik; Regelbindung versus Diskretion; Öffentliche Meinung; Asymmetrische Information; Zeitkonsistenz; Neoklassische Synthese; Zustandsraummodell; Theorie